Study on land use change and driving force in Chengdu-Chongqing urban agglomeration - Wang Miao; Wang Ling (ITM Web of Conferences, 2022)
The study of land use change and its driving forces at urban agglomeration scale is one of the most urgent issues to be studied.Based on GlobeLand30 data set of 2000, 2010 and 2020, this paper uses ArcGIS and other software to calculate and process land use change in Chengdu- Chongqing urban agglomeration and its driving forces through dynamic attitude and transfer matrix.The results showed that :(1) the land use change in chengdu-chongqing urban agglomeration was significant from 2000 to 2020, and the area of construction land continued to increase and the change rate was fast, while the area of cropland and grassland decreased.(2) The main drivers are population growth, socio-economic development and policy factors.The results provide references for the allocation of land resources and sustainable land use in this region.